Soluble fms-like tyrosine kinase 1, placental growth factor and procalcitonin as biomarkers of gram-negative sepsis: Analysis through a derivation and a validation cohort. Issue 44 (5th November 2021) - Vittoros, Vasileios; Kyriazopoulou, Evdoxia; Lada, Malvina; Tsangaris, Iraklis; Koutelidakis, Ioannis M.; Giamarellos-Bourboulis, Evangelos J.
Abstract : Abstract: Further improvement of the diagnostic and prognostic performance of biomarkers for the critically ill is needed. Procalcitonin (PCT), placental growth factor (PlGF) and soluble fms-like tyrosine kinase-1 raise interest for sepsis diagnosis and prognosis. Serum samples from 2 cohorts of 172 patients (derivation cohort) and of 164 patients (validation cohort) comprising only patients with microbiologically confirmed gram-negative infections were analyzed. PlGF, s-Flt-1 and procalcitonin (PCT) were measured in serum within 24 hours from sepsis onset and repeated on days 3 and 7. PCT and s-Flt-1 baseline levels were higher in sepsis and septic shock compared to non-sepsis; this was not the case for PlGF. s-Flt-1 at concentrations greater than 60 pg/ml diagnosed sepsis with sensitivity 72.3% and specificity 54.9% whereas at concentrations greater than 70 pg/ml predicted unfavorable outcome with specificity 73.0% and sensitivity 63.7%. At least 80% decrease of PCT and/or PCT less than 0.5 ng/ml on day 7 was protective from sepsis-associated death. Both s-Flt-1 and PCT should be measured in the critically ill since they provide additive information for sepsis diagnosis and prognosis. ClinicalTrials.gov numbers NCT01223690 and NCT00297674.